Espiritualidade e sentido de vida: importância para o funcionamento saudável. - Silva, Andreia Barbosa da (2020)
The dissertation, developed in two studies, investigates the importance of the relationship between spirituality and the meaning of life, as well as its impacts on healthy functioning. The first study sought to map the scientific production in Psychology